1991
DOI: 10.1164/ajrccm/143.3.476
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Response to Arm Elevation in Patients with Chronic Airflow Obstruction

Abstract: We have shown that patients with chronic airflow obstruction (CAO) complain of disabling dyspnea when performing seemingly trivial tasks with unsupported arms. Surprisingly little is known about the metabolic and ventilatory responses to unsupported upper extremity activity even though some of the muscles of the upper torso and shoulder girdle are used to perform simple and complex everyday tasks as well as partake in ventilation. To determine the effect of simple arm elevation in 20 patients with CAO we studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 11 publications
2
42
1
Order By: Relevance
“…This is in accordance with earlier studies [5,8], although the percentage increases in V'O 2 , V'CO 2 , V'E and HR in these studies were much higher than reported here. Instead of calculating peak metabolic and ventilatory response in these earlier studies, we calculated the mean increase of the total period of arm elevation and recovery.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This is in accordance with earlier studies [5,8], although the percentage increases in V'O 2 , V'CO 2 , V'E and HR in these studies were much higher than reported here. Instead of calculating peak metabolic and ventilatory response in these earlier studies, we calculated the mean increase of the total period of arm elevation and recovery.…”
Section: Discussionsupporting
confidence: 94%
“…This was confirmed in a study by DOLMAGE et al [4], who found that even arm positioning only (arms elevated but supported by a sling) changed breathing pattern in COPD patients (decrease in VT, increase in f R). In addition, MARTINEZ et al [8] found that except for an increased diaphragmatic recruitment, COPD patients probably also recruite expiratory muscles during arm elevation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible cause of dyspnea is the change in lung volumes (decreased FVC and inspiratory capacity, and increased functional residual capacity) during upper-limb activities. 12,33 Also, reduction of blood flow during elevation of the upper limbs increases the production of lactate, which increases ventilation demand and, consequently, dyspnea. 34,35 One of the most common measures of muscle fatigue is the decline in maximum strength.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is unlikely that IPV decreased dyspnea by decreasing vagal afferent signals. In COPDpatients, upper inspiratory intercostal muscles are suggested to be tonically active during AE (9), and may contribute to the increase in functional residual capacity (FRC) (19). Increasing hyperinflation during leg exercise has been indicated to be related to dyspnea in COPDpatients (20).…”
Section: Central Motor Commandmentioning
confidence: 99%